The Silent Garden : Raising Your Deaf Child - Ogden, Paul W. (Book collections on Project MUSE., 1996)
"The Silent Garden provides parents of deaf children with crucial information on the greater possibilities afforded their children today. Deaf since birth, Paul Ogden, a professor of Deaf Studies, offers parents a firm foundation for making the difficult decisions necessary to begin their child on the road to realizing his or her full potential. This encouraging book first helps parents to address critical concerns right away, such as how to communicate with their child. It then guides parents on issues such as what type of school their child can attend, what kinds of professional help are beneficial to the family, and what technological alternatives are available. Case studies and interviews with parents of deaf children help to reassure parents that they can prepare their child for a full, productive life."--Jacket.